Peningkatan Minat Baca Melalui Penggunaan Media Video Animasi Pada Mata Pelajaran Bahasa Indonesia Kelas V SD GMIT Manumuti - Novita Mali Laku, Jeni; Fembriani; Netty E. A. Nawa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low reading interest of fifth-grade students at SD GMIT Manumuti, which was reflected in students’ lack of enthusiasm for reading activities both independently and during Indonesian language learning. This condition affected students’ participation and engagement in classroom learning activities. The purpose of this study was to improve students’ reading interest through the use of animated video media in Indonesian language learning. The study employed Classroom action research (CAR) using the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection stages implemented in two cycles. The participants were 21 fifth- grade students of SD GMIT Manumuti. Data were collected through observation, questionnaires, interviews, and documentation. The data were analyzed using descriptive quantitative and qualitative techniques. The findings revealed that the implementation of animated video media successfully improved students’ reading interest. In the inital condition, most students demonstrated low reading interest. After the implementation of cycle I, the classical completeness reached 47.6% with an average score of 73.80%. Furthermore, in cycle II, students’ reading interest increased significantly, reaching an average score of 90.83% and a classical completeness rate of 85.71%. These findings indicate that animated video media is effective in enhancing students’ reading interest in Indonesian language learning at the elementary school level.